Enhancement of the Mechanical Properties of Hydroxyapatite/Sulphonated Poly Ether Ether Ketone Treated Layer for Orthopaedic and Dental Implant Application - Roohollah Sharifi; Davood Almasi; Izman Bin Sudin; Mohammed Rafiq Abdul Kadir; Ladan Jamshidy; Seyed Mojtaba Amiri; Hamid Reza Mozaffari; Maliheh Sadeghi; Fatemeh Roozbahani; Nida Iqbal (International Journal of Biomaterials)
The mechanical properties of coated layers are one of the important factors for the long-term success of orthopeadic and dental implants. In this study, the mechanical properties of the porous coated layer were examined via scratch and nanoindentation tests. The effect of compression load on the porous coated layer of sulphonated poly ether ether ketone/Hydroxyapatite was studied to determine whether it changes its mechanical properties. The water contact angle and surface roughness of the compressed coated layer were also measured. The results showed a significant increase in elastic modulus, with mean values ranging from 0.464 GPa to 1.199 GPa (p<0.05). The average scratch hardness also increased significantly from 69.9 MPa to 95.7 MPa after compression, but the surface roughness and wettability decreased significantly (p<0.05). Simple compression enhanced the mechanical properties of the sulphonated poly ether ether ketone/hydroxyapatite coated layer, and the desired mechanical properties for orthopaedic and dental implant application can be achieved.